ChemInform Abstract: An All‐Metal Aromatic Sandwich Complex [Sb3Au3Sb3]3‐. Issue 52 (10th December 2015) - Pan, Fu‐Xing; Li, Lei‐Jiao; Wang, Ying‐Jin; Guo, Jin‐Chang; Zhai, Hua‐Jin; Xu, Li; Sun, Zhong‐Ming
Abstract: Dark red crystals of [K([2.2.2]cryptand)]3 [Sb3 Au3 Sb3 ] ·0.5PPh3 ·en (I) are prepared by addition of a toluene solution of Au(PPh3 )Ph to a solution of K5 Sb4 and [2.2.2]cryptand in en (25 °C, 4 h; 11% yield).